2022
DOI: 10.1089/wound.2021.0118
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Hospitalizations and Amputations in Patients with Diabetic Foot Ulcers Treated with Cyclical Pressurized Topical Wound Oxygen Therapy: Real-World Outcomes

Abstract: Background: This study sought to examine the real-world impact of multimodality cyclical-pressure topical wound oxygen therapy (TWO2) on hospitalizations and amputations in patients with diabetic foot ulcer (DFU) compared with patients without TWO2. Methods: We conducted a retrospective review of deidentified patient medical records at 2 U.S. Veterans Affairs hospitals between January 2012 and January 2020. DFU patients were assigned to TWO2 or NO TWO2 cohorts based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The results show that patients who received indigenous NPWT with added topical pressurised oxygen therapy achieved the highest mean wound area and depth reduction, and increased sterile cultures of infected wounds after treatment. A matched cohort study by Yellin et al 35 concluded that the control group (no TWO2) had nearly nine times higher risk of hospitalisation and five times higher risk of amputation compared with the TWO2 group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results show that patients who received indigenous NPWT with added topical pressurised oxygen therapy achieved the highest mean wound area and depth reduction, and increased sterile cultures of infected wounds after treatment. A matched cohort study by Yellin et al 35 concluded that the control group (no TWO2) had nearly nine times higher risk of hospitalisation and five times higher risk of amputation compared with the TWO2 group.…”
Section: Resultsmentioning
confidence: 99%
“…An RCT by Moffatt et al 40 demonstrated that the use of Oxyzyme dressings resulted in decreased mean costs per patient. Although cost‐effectiveness was not one of the aims of the study, findings from a retrospective cohort study by Yellin et al 35 suggest that patients that were not treated with TWO2 had nine times higher risk of hospitalisation and five times higher risk of amputation compared to the group treated with TWO2 which would imply that TOT may lead to reduced costs as hospitalisation significantly increases associated treatment costs. More research is needed to better understand the cost implication of using TOT for the treatment of wounds.…”
Section: Discussionmentioning
confidence: 99%
“…The other method is Topical oxygen therapies (TOTs), which deliver oxygen directly to the open wound 86 . Compared with systemic HBOT, it has the advantages of strong patient compliance, small equipment footprint, and low cost 70,87,88 …”
Section: Physical Therapy Of Dfumentioning
confidence: 99%
“…Regulating blood glucose levels and appropriate insulin therapy have shown high efficacy in wound closure ( Veves et al, 2001 ). Other methods, such as revascularization ( Liu et al, 2019 ), hyperbaric oxygen therapy ( Raspovic et al, 2022 ), and granulocyte colony-stimulating factor ( Yellin et al, 2022 ), have also been used. However, in most cases, wound dressings create an optimal environment for open wounds, leading to better and faster wound closure ( Futrega et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%